Pengaruh Penambahan Fly Ash dan Serbuk Kaca Terhadap Sifat Fisik dan Mekanik Komposit Batako - Husain, La Ode; Endriatno, Nanang; Aminur, Aminur (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2020)
Composite  is  a  new  material  engineered  by  two  or  more  materials  where  the properties of the materials differ from one another both in chemical and physical properties. Composites are obtained from a combination of metal with ceramics, metal with plastics,  and others. The purpose of this study was to determine the effect of adding fly ash and glass powder on the physical and mechanical properties of  brick-based  composites.  The  drying  process  is  carried  out  for  28  days.  The compressive strength and water absorption tests were carried out after the drying process.  The  results showed  the  highest  compressive strength  value  is  on  the  B sample  is  74.17  kg  /  cm2  and  water  uptake  is  lowest  in  the  sample  A,  namely 10.53%. The highest compressive strength test results exist in the sample B is 74.17 kg / cm2 and the compressive strength is lowest in the sample A which is 66.67 kg / cm2. While the highest water absorption test results were in sample C, namely 15.05% and the lowest water absorption value was in sample A, namely 10.53%. Keywords:  Brick-Based,  fly  ash,  glass  powder,  compressive  strength,  water absorption.